NLRC5 Functions beyond MHC I Regulation—What Do We Know So Far? - Benkő, Szilvia; Kovács, Elek Gergő; Hezel, Felix; Kufer, Thomas A. (Frontiers in Immunology, 2017)
NLRC5 is a member of the NLR-family that acts as a transcriptional activator of MHC class I genes. In line with the function of several related NLR proteins in innate immune responses, there is, however, also ample evidence that NLRC5 contributes to innate and adaptive immune responses beyond the regulation of MHC class I genes. In human and murine cells, for example, NLRC5 was proposed to contribute to inflammatory and type I interferon responses. The role of NLRC5 in these and other cellular processes is hitherto still not well understood and blurred by discrepancies in the reported data. Here we provide a detailed and critical discussion of the available experimental data on the emerging biological functions of NLRC5 in innate immune responses in men and mice. Better awareness of the multiple roles of NLRC5 will help to define its overall contribution to immune responses and cancer.